2017
DOI: 10.7150/thno.17069
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Internalization via Endocytosis Inducing S-Phase Arrest and Priming Maver-1 Lymphoma Cells for Cytarabine Chemotherapy

Abstract: The goal of precision therapy is to efficiently treat cancer without side effects. Aptamers are a class of small ligands composed of single-stranded oligonucleotides that bind to their targets with high affinity and specificity. In this study, we identified an ssDNA aptamer specifically targeting Maver-1 lymphoma cells with high binding affinity (Kd = 70±8 pmol/L). Interestingly, cellular cycle studies revealed that exposure of Maver-1 cells to synthetic aptamers triggered S-phase arrest of 40% of the cells (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The S phase cell cycle check point ensures synthesis of DNA and proteins and is a crucial regulator of cell cycle progression, while the G2/M checkpoint allows cells to enter mitosis [ 34 , 35 ]. Cyclin D1 and p21 cyclin-dependent kinases are major regulators of S phase progression [ 36 38 ]. Recent studies showed the transcriptionally repressive ZNF-KRAB domain can recruit KRAB-associated protein-1 (KAP1) [ 12 , 13 , 39 ] and other co-repressors, and KRAB-ZFP forms heterochromatin with chromobox 5 (CBX5), SET domain bifurcated 1 (SETDB1) and various histone deacetylases (HDACs) to epigenetically silence KRAB-ZNF target genes [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S phase cell cycle check point ensures synthesis of DNA and proteins and is a crucial regulator of cell cycle progression, while the G2/M checkpoint allows cells to enter mitosis [ 34 , 35 ]. Cyclin D1 and p21 cyclin-dependent kinases are major regulators of S phase progression [ 36 38 ]. Recent studies showed the transcriptionally repressive ZNF-KRAB domain can recruit KRAB-associated protein-1 (KAP1) [ 12 , 13 , 39 ] and other co-repressors, and KRAB-ZFP forms heterochromatin with chromobox 5 (CBX5), SET domain bifurcated 1 (SETDB1) and various histone deacetylases (HDACs) to epigenetically silence KRAB-ZNF target genes [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…They exploit this effect in a combined treatment of lymphoma cells with a cytotoxic cytarabine. The lethal action of cytarabine is predominant over lymphoma cells in S-phase, and they show that several rounds of aptamer treatment was able to synergistically sensitize these cells to the lethal effect of cytarabine [68].…”
Section: Tumor-targeted Aptamers Complexed Directly To Sirnas and Othmentioning
confidence: 94%
“… 117 , 118 Li et al. 119 developed a ssDNA aptamer that can specifically target Maver-1 lymphoma (B cell lymphoma) cells and Ig lambda-like polypeptide. The functional studies revealed selective internalization of aptamers into Maver-1 lymphoma cells, triggering cell cycle S-phase arrest and cellular growth inhibition.…”
Section: Main Textmentioning
confidence: 99%
“…These results demonstrate the importance of aptamers in synergistic biotherapy via cell cycle regulation and chemotherapy of lymphoma. 119 …”
Section: Main Textmentioning
confidence: 99%